Educational use of Facebook by undergraduate students in Malaysia higher education: A case study of a private university - Lee, Cheng Ean Catherine *; Teh, Phoey Lee * (Lectito, 2016)
The learning environments in higher education are moving towards the integration of information and communication technology (ICT) such as social media. Recent years have witnessed an increased interest of using social media in higher education and this has created a growing phenomenon for the educational use of social networking sites such as Facebook, to create, engage, and share information among the students. This paper presents a qualitative analysis of the Facebook closed group activities of undergraduate students in a Malaysian private university. The analysis of data shows four main themes of students' education related use of Facebook closed group and issues relating to students’ use of Facebook for educational purposes due to its increasing prevalence in the everyday lives of students. This paper concludes with two main findings of the realities of students' Facebook closed group activity and the role of Facebook in students' experience in higher education.